EFEKTIFITAS PENDIDIKAN BENCANA TERHADAP KAPASITAS EVAKUASI DIRI DARI DALAM KELAS SAAT GEMPA BUMI SISWA TK RA. AL-MUNAWWAROH LEMBANG: THE EFFECTIVENESS OF DISASTER EDUCATION ON THE CAPACITY OF SELF-EVACUATION FROM THE CLASSROOM DURING AN EARTHQUAKE OF KINDERGARTEN RA STUDENTS. AL-MUNAWWAROH LEMBANG - Triwulan Anggraeni; Untung Sudharmono (Jurnal Kesehatan, 2023)
Earthquakes due to the movement of the Lembang fault are potential major disasters that threaten the people of Lembang District, West Bandung Regency. The potential for earthquakes due to the Lembang fault is predicted at 6.8 on the Richter scale. Children are a group of people who are vulnerable groups, so it is necessary to increase children's capacity in facing disaster threats. The purpose of the study was to see the effectiveness of disaster education on self-evacuation capacity from inside the classroom during the Earthquake of RA Kindergarten Students. AL-MUNAWWAROH Lembang. The method used is descriptive quantitative with the research design of Earthquake Disaster Simulation Observation. The respondents in this study were 21 students. This research instrument uses observation sheets to document student behavior during earthquakes. Disaster education materials are delivered with power point media delivered through laptops and LCD impressions. The results of the data obtained as many as 85% of kindergarten students. RA. AL-Munawwaroh Lembang, West Bandung Regency has the capacity to evacuate themselves from the classroom during an earthquake. The conclusion of this study is that disaster education delivered through material exposure and simulation can be used to increase self-evacuation capacity from inside the classroom during an earthquake of RA Al-Munawwaroh Lembang Kindergarten students